Penentuan Perbandingan Volume Fasa Membran dan Volume Fasa Internal serta Lama Waktu Ekstraksi pada Proses Ekstraksi Ion Merkuri Menggunakan Teknik Emulsi Membran Cair - Genefefa T., Fulgensia; Hamzah, Baharuddin; Ningsih, Purnama (Jurnal Akademika Kimia, 2017)
This study aimed to determine the optimum condition on the extraction process of mercury ions with the variables of study on the ratio of membrane phase volume and internal phase volume (Mp:Ip) and the extraction time which will provide the greatest percent extraction. Sample used in this study was an artificial sample containing Hg(II) ions with a concentration of 10 mg/L. Hg(II) ions will be distributed into internal phase through membrane phase formed from a mixture of surfactants, kerosene and chelating compounds. Concentration of mercury ions remained in the samples was analyzed using a UV-VIS spectrophotometer at a wavelength of 490 nm with ditizon as a complex. The optimum condition was achieved at a volume ratio of membrane phase (Mp) with internal phase (Ip) of 2:2, and the extraction time was for 10 minutes, where percent extractions were 66.11% and 82.23%, respectively.